IR and Vendors: Selecting the Right Product. Issue 178 (23rd November 2018) - Ferland, Christopher; Flachbarth, Justin
Abstract: The market is full of vendors selling products each designed to solve institutional problems. But how does one choose the right tool for their institution and situation? Topics addressed in this chapter include: how to gauge institutional needs, how to evaluate products, and understand the available institutional resources (current and future). The chapter concludes by offering six suggestions for IR offices (and professionals) when they start to consider vendor products.